Pelatihan Senam Otak Untuk Mencegah Demensia Pada Lansia - Sontina Saragih; Yusuf Hanafiah (Pusat Riset dan Inovasi Nasional, 2023)
Elderly or old age is a period where a person enters 60 years and over. Elderly people generally experience a decline in bodily function, one of the most common declines in bodily function is cognitive function. There are various diseases caused by cognitive disorders. One disease or health problem that is often experienced by the elderly is dementia. Dementia is a progressive disease that cannot be cured. Patients with advanced dementia will experience the last year of their life with various problems and persistent severe disabilities. One way to prevent dementia is by doing brain exercises. Brain exercise is a simple body movement-based exercise that can be done anywhere and at any time. The population of this community service is the elderly in the Sei Sikambing sub-district, Medan Sunggal sub-district. The implementation method used in this community service is the PAR (Participatory Action Research) method. In this method, the service carried out has the aim of empowerment, namely training participants' independence from community service. The number of elderly male respondents was 18 people and elderly women were 12 respondents. After conducting brain exercise training interventions for the elderly and providing material about dementia, a posttest was carried out again to assess the development of knowledge received by respondents.